Pictures of Rural Education: images about the paths that lead to schools in Paraense Amazon - Joana Darc de Neves; Antonio Pinheiro; Alessandra Sampaio Cunha; Tania Suely Azevedo Brasileiro (Universidade Federal do Norte do Tocantins, 2020)
This article brings forward the discussions about the images about the paths that lead to Rural Schools in the Paraense Amazon. For such, the meanings constructed by children in early childhood education about the paths that are taken to school were analyzed. The theoretical foundation is based especially in Caldart (2004), Molina and Sá (2011) and Hage (2005). Methodologically, it presents a qualitative approach in the psychosocial field, in a dialectical movement that involves the objective and subjective world, as a constituent process of images and constructed meanings. For the analysis, the contexts surrounding the reality of Rural Education Education experienced by children from a municipality in the Amazon region of Pará were considered, as were the meanings that the children studied attribute to this path based on their drawings and the arguments that justifythe images of the paths that lead to school. The revealed results the intersubjective dialectical movement, constituent and constructor of the reality of values that imprint a rupture of the dynamics between nature and the school's artificial world in the reality of the Paraense Amazon, highlighting the importance of considering the subjectivity of the rural subjects as a political act to propose their training and educational policies.